Low-density lipoprotein cholesterol levels on admission and long-term outcomes in statin-naive patients with acute coronary syndrome. (25th November 2020) - Satou, R; Matsuzawa, Y; Akiyama, E; Konishi, M; Yoshii, T; Okada, K; Maejima, N; Iwahashi, N; Hibi, K; Kosuge, M; Ebina, T; Tamura, K; et al.
Abstract: Introduction: Dyslipidemia, especially an increase in the low-density lipoprotein cholesterol (LDL-C) has been established as one of the most important risk factors for atherosclerotic cardiovascular diseases. In contrast, some recent studies have shown that the low LDL-C level was associated with short-term poor prognosis in patients with cardiovascular disease, and this is so-called "cholesterol paradox". However, there is few data evaluating the effects on long-term outcome of "cholesterol paradox" in patients with acute coronary syndrome (ACS). Purpose: The purpose of this study was to examine whether the low LDL-C level on admission affect long-term prognosis in patients with ACS. Methods: A total of 434 ACS patients who survived to hospital discharge were enrolled in this study. All patients were statin-naïve on admission, and were received statin therapy after hospitalization. Patients were divided into the low LDL-C (≤114 mg/dl) and high LDL-C (>114 mg/dl) groups using the first tertile of the LDL-C level on admission. The primary endpoint was composite outcomes of all-cause death, myocardial infarction, ischemic stroke, hospitalization for congestive heart failure and unplanned revascularization. Results: During a median follow-up period of 5.5 years, primary endpoint occurred in 117 patients. Overall, event-free rates differed significantly between the low and high LDL-C groups, demonstrating the lower event-free rate in patients with the low LDL-C group (38.9% in low LDL-C group versus 20.7% in high LDL-C group, p=0.0002; Figure). Even after adjustment for age, sex, body mass index, and various classical risk factors, the low LDL-C group was significantly at higher risk for primary composite outcomes compared to the high LDL-C group (adjusted hazard ratio 1.65, 95%-confidence interval 1.10–2.49, p=0.02). Conclusion: In patients with ACS, the low LDL-C level on admission was significantly associated with long-term worse prognosis, regardless of statin therapy at discharge. In ACS patients with low LDL-C level, it might be necessary for elucidating the residual risk for secondary adverse event to improve their prognosis. Funding Acknowledgement: Type of funding source: None